2012
DOI: 10.1007/s13181-012-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

Toxico-Surveillance of Infant and Toddler Poisonings in the United States

Abstract: Infant and toddler poisonings are important to capture and may be challenging to manage. We aim to describe the Toxicology Investigators Consortium (ToxIC) Case Registry as a tool for toxico-surveillance of this problem in the United States. Using the ToxIC Case Registry database of the American College of Medical Toxicology, we identified infant and toddler poisonings over a 15-month period between April 1, 2010 and June 30, 2011 reported to the 31 Registry sites. Of 6,810 poisoning cases reported to the ToxI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…We have previously reported that 1 in 8 children <2 years assessed by medical toxicology services in emergency departments in the United States had been exposed to illicit drugs or alcohol. 11 Some limitations of our work should be noted. Chief among these is that our database allows linkage of children with their mothers based on birth records, but does not allow identification of father-child nor sibling-child pairs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have previously reported that 1 in 8 children <2 years assessed by medical toxicology services in emergency departments in the United States had been exposed to illicit drugs or alcohol. 11 Some limitations of our work should be noted. Chief among these is that our database allows linkage of children with their mothers based on birth records, but does not allow identification of father-child nor sibling-child pairs.…”
Section: Discussionmentioning
confidence: 96%
“…Young children are particularly prone to unintentional overdoses involving substances in their immediate environment and, less commonly, as victims of neglect or malice. 11 To determine the potential downstream impact of parental opioids prescribing on their young children, we explored whether maternal receipt of prescription opioids is associated with an increased risk of overdose harm to young children in the home.…”
Section: What This Study Addsmentioning
confidence: 99%
“…5 Studies of pediatric poisonings usually group all infants <1 year of age together. 1,[6][7][8][9] However, there is a large variation in motor abilities within the first year of life. 10 An infant who is not yet sitting upright would have a limited potential for exploration compared with one who is cruising or walking.…”
mentioning
confidence: 99%
“…6,7 ToxIC includes 37 sites from 21 states across the United States, the majority of which are university-affiliated academic institutions, including 20 (87%) of the 23 currently active national medical toxicology fellowship training programs. Participating sites prospectively register all cases managed by medical toxicologists at the bedside into an online, passwordprotected database, which is maintained centrally by the American College of Medical Toxicology.…”
Section: Settingmentioning
confidence: 99%
“…A detailed description of the registry has been published, 6 and its findings previously reported. [7][8][9] alcohol or illicit drug exposure or of prescription drug misuse. The latter is defined by the National Survey on Drug Use and Health as "use of any form of prescription drugs that were not prescribed for the [patient] or that the [patient] took only for the experience they caused."…”
Section: Settingmentioning
confidence: 99%